Managing operations across the supply chain - Swink, Morgan 1959-; Melnyk, Steven A.; Hartley, Janet L. (Janet Lea) (New York McGraw-Hill, 2024)
We continue to live in dynamic and exciting times. Recent years have seen many changes that have affected nearly every aspect of business, including operations management. In this fifth edition of our book, we continue to reflect key shifts in operations management, including transitions: From a focus on the internal system to a focus on the supply chain. In today's highly competitive business environment, organizations must leverage the capabilities of their suppliers and customers. Operations managers must look beyond the "four walls" of the firm and take an integrated supply chain perspective of operations. From a local focus to a global focus. As Thomas L. Friedman pointed out, the world is indeed flat. Business solutions generated in Argentina are used to meet needs in the United States, and parts built by suppliers located in China are used to assemble cars in Canada. Commercial needs have overcome, to a large part, national borders, presenting new opportunities and challenges for operations managers"--Provided by publisher.
Includes index.
Keywords: Business logistics; Industrial management; Production management